Minat Baca dengan CIRC dan Mind Mapping - Faraola, Hala; Salim, Herli (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The students' low reading interest is a matter of concern. Where reading is the most important thing in learning activities. Therefore, it is necessary to have an appropriate and creative strategy or method so that the expected learning objectives are achieved. CIRC is a learning model that collaborates cooperative reading and writing activities. Combined with the Mind Mapping method which involves student creativity. Based on research in class V SDN Pondokkaso Tonggoh, CIRC and Mind Mapping provide a good stimulus for students' reading interest, especially in Indonesian language learning. The purpose of this study was to determine whether or not the CIRC model and the Mind Mapping method affected reading interest. This research was conducted during the outbreak of the Covid-19 virus, so there are several adjustments in this study. The research conducted was a quasi-experimental study with a nonequivalent control group design. The study population was all students in class V and the sample taken was the VA class which was divided into the experimental class and the control class. The data collection techniques used were pre and post-test, Likert scale questionnaire, and observation. Based on the data collected, it was found that the average experimental class students experienced a significant increase in reading interest, from the initial average of 87.43 to 92.07 while in the control class the initial average of 85.79 became 88.07. At the time of learning, students in the experimental class were calmer than the control class, this made the experimental class get better results.